AN EVALUATION OF MOBILE-GOVERNMENT WEBSITES IN INDONESIA - Harry Noor Sukarna (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2015)
This research evaluates 20 mobile-government websites in Indonesia based on the evaluation framework consists of four aspects, namely General Characteristics, E-Content, E-Services and E-Participation. Based on the evaluation result, all the mobile-government websites focus on e-content and e-participation. The content here is updated regularly especially about news and information, however the low e-services scores provide evidence that the content and e-participation provided are one-way communication method only. Mobilegovernment implementation in Indonesia seems still in the first stage of e-government development model. Most of the mobile webs are only informational. It is suggested to improve and develop further to reach the transactional level where all the services are integrated. Keywords: m-government, e-government, website evaluation, mobile website evaluation, Indonesia